2020
DOI: 10.1105/tpc.19.00970
|View full text |Cite
|
Sign up to set email alerts
|

Specific Recruitment of Phosphoinositide Species to the Plant-Pathogen Interfacial Membrane Underlies Arabidopsis Susceptibility to Fungal Infection

Abstract: Plant biotrophic and hemibiotrophic pathogens modulate cellular distribution of host phosphoinositides and recruit PI(4,5)P 2 to the plant-pathogen interfacial membrane as a susceptibility factor for disease development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 118 publications
3
41
0
Order By: Relevance
“…The EHM was found to differ in its molecular composition from the conventional PM (Hückelhoven & Panstruga, 2011;Gil & Gay, 1977;Roberts et al, 1993;Micali et al, 2011;Koh et al, 2005). Remarkably, two recent studies reported that the EHM is enriched in PI(4,5)P 2 similarly as described in this study for the pollen endo-PM (Shimada et al, 2019;Qin et al, 2020). Future work on the pollen endo-PM needs to track the genesis of this special interface during male gamete differentiation and to investigate its functional significance.…”
Section: The Endo-pm Of the Pollen Vegetative Cell Is Enriched For Pisupporting
confidence: 68%
“…The EHM was found to differ in its molecular composition from the conventional PM (Hückelhoven & Panstruga, 2011;Gil & Gay, 1977;Roberts et al, 1993;Micali et al, 2011;Koh et al, 2005). Remarkably, two recent studies reported that the EHM is enriched in PI(4,5)P 2 similarly as described in this study for the pollen endo-PM (Shimada et al, 2019;Qin et al, 2020). Future work on the pollen endo-PM needs to track the genesis of this special interface during male gamete differentiation and to investigate its functional significance.…”
Section: The Endo-pm Of the Pollen Vegetative Cell Is Enriched For Pisupporting
confidence: 68%
“…PtdIns(4,5)P 2 accumulates in Arabidopsis plants at sites of pathogen infection (Shimada et al ., 2019; Qin et al ., 2020), and PtdIns(4,5)P 2 was identified as a susceptibility factor in Arabidopsis (Qin et al ., 2020). Therefore, the induction of StIPP, an enzyme hydrolyzing PtdIns(4,5)P 2 at the EHM, might be part of a defensive strategy of the host plant that involves limiting the availability of PtdIns(4,5)P 2 at infection sites.…”
Section: Discussionmentioning
confidence: 99%
“…A role for phosphoinositides in plant pathogen defense was recently proposed based on the observation that a fluorescent reporter for PtdIns(4,5)P 2 as well as a PI4P 5-kinase mediating the biosynthesis of PtdIns(4,5)P 2 accumulated in extra-invasive hyphal membranes upon infection of Arabidopsis thaliana with the pathogenic fungus Colletotrichum higginsianum (Shimada et al, 2019). Moreover, Qin et al (2020) recently identified PtdIns(4,5)P 2 as a susceptibility factor associating with the EHM after powdery mildew infection of Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, a contribution of phosphoinositides to the regulation of important physiological processes has also been reported for the vegetative portion of plants. These studies describe roles for phosphoinositides in clathrin recruitment (König et al, 2008;Ischebeck et al, 2013); the polarization of auxin efflux carriers of the PIN-FORMED (PIN)-family (Mei et al, 2012;Ischebeck et al, 2013; Tejos et al, 2014), of D6P-kinases (Barbosa et al, 2016) and of BRX and PAX proteins (Marhava et al, 2020); the control of cytokinesis (Lin et al, 2019); cell wall deposition (Rodriguez-Villalon et al, 2015), and roles in membrane trafficking during plant pathogen interactions (Shimada et al, 2019;Qin et al, 2020). While these reports together may suggest the presence of PtdIns(4,5)P 2 in membrane nanodomains occupied by phosphoinositides, in Arabidopsis hypocotyl cells we detected such nanodomains by SD only upon application of salt (Supplemental Fig.…”
Section: Ptdins(45)p 2 Nanodomains Only In Pollen Tubes and Other Opmentioning
confidence: 99%